Encouraging translation and assessing impact of the Centre for Research Excellence in Integrated Quality Improvement: rationale and protocol for a research impact assessment. Issue 12 (4th December 2017) - Ramanathan, Shanthi; Reeves, Penny; Deeming, Simon; Bailie, Ross Stewart; Bailie, Jodie; Bainbridge, Roxanne; Cunningham, Frances; Doran, Christopher; McPhail Bell, Karen; Searles, Andrew
Abstract : Introduction: There is growing recognition among health researchers and funders that the wider benefits of research such as economic, social and health impacts ought to be assessed and valued alongside academic outputs such as peer-reviewed papers. Research translation needs to increase and the pathways to impact ought to be more transparent. These processes are particularly pertinent to the Indigenous health sector given continued concerns that Indigenous communities are over-researched with little corresponding improvement in health outcomes. This paper describes the research protocol of a mixed methods study to apply FAIT (Framework to Assess the Impact from Translational health research) to the Centre for Research Excellence in Integrated Quality Improvement (CRE-IQI). FAIT will be applied to five selected CRE-IQI Flagship projects to encourage research translation and assess the wider impact of that research. Methods and analysis: Phase I will develop a modified programme logic model for each Flagship project including identifying process, output and impact metrics so progress can be monitored. A scoping review will inform potential benefits. In phase II, programme logic models will be updated to account for changes in the research pathways over time. Audit and feedback will be used to encourage research translation and collect evidence of achievement of any process, output and interim impacts. In phase III, three proven methodologies for measuring research impact—Payback, economic assessment and narratives—will be applied. Data on the application of FAIT will be collected and analysed to inform and improve FAIT's performance. Ethics and dissemination: This study is funded by a nationally competitive grant (ID 1078927) from the Australian National Health and Medical Research Council. Ethics approval was obtained from the University of Newcastle's Human Research Ethics Committee (ID: H-2017–0026). The results from the study will be presented in several peer-reviewed publications, through conference presentations and via social media.